KONSEP EKONOMI KERAKYATAN MOHAMMAD HATTA DALAM TINJAUAN MAQASID SYARI’AH - Sitti Muallimah (FEBI IAIN Langsa, 2018)
This study focuses on the concept of people’s economy from Muhammad Hatta reviewed in Maqasid al-Shariah’s perspective. Hatta’s attention to the people who were downtrodden due to the socio-economic structure in the Dutch colonization era backed by aristocrats and feudalism has led him to develop cooperatives. This study aims to describe the concept of people’s economy by Muhammad Hatta and analyze the relevance of Muhammad Hatta’s concept from Maqasid al-Shariah’s perspective. The study is a library research using the data obtained from primary and secondary sources. Based on the results and analysis, it is concluded that: According to Hatta, the concept of people’s economy is cooperatives. Cooperative is a from of joint venture by people to achieve mutual objectives. Cooperative was proposed based on the facts in the Dutch colonization era. Hatta as a founding father has brought the people’s economy to reality in the from of cooperatives as reflected by Article 33 of the 1945 Constitution. Hatta’s thoughts are relevant to the objectives of Islam 68 (Maqaashid al-Shariah). Among the basic values emphasized by Hatta are the values of ownership, justice, togetherness and familiarity, economic cooperation and cooperative, economic democracy and government’s role.